Understanding the effects of recreational catch‐and‐release angling on an increasingly important foreign fishing tourism species, the giant African threadfin Polydactylus quadrifilis (Cuvier) - Edward Claude Butler; Amber‐Robyn Childs; Murray Ian Duncan; Warren Mason Potts (Fisheries Management and Ecology, 2020)
Foreign fishing tourism (FFT) is becoming increasingly popular in the developing world, where it often coexists alongside other important sectors involving domestic recreational anglers and dependant artisanal and subsistence fishing communities. Therefore, it is important that FFT operations use effective catch‐and‐release (C&R) angling to minimise negative impacts to locally important fishery species. Using reflex action mortality predictors (RAMPs) and physiological stress indicators, this study assessed the impacts of C&R angling within the FFT fishery targeting Polydactylus quadrifilis (Cuvier) on the Kwanza Estuary, Angola. Air exposure (cumulative link model (CLM): Z = 3.99, p p = 0.02) significantly predicted increased motor impairment. Handling practices were particularly important for larger reproductively valuable individuals as fish size was positively correlated with fight (Spearman's rank: r = 0.85, p r = 0.70, p